Bimbingan Penerimaan Diri Remaja Broken Home - Fahrurrazi Fahrurrazi; Casmini Casmini (Program Studi Bimbingan dan Konseling Islam IAIN Langsa, 2020)
This study aims to determine the process of experience that makes the subject re-accept himself and the guidance obtained by the subject so that he is able to accept himself again. This research is a phenomenological qualitative study with a single informant who does experience broken home families. Data collection was carried out by interview and observation. Data analysis techniques used data reduction, data presentation and drawing conclusions. The results of this study indicate that the process of experience gained through pre-broken home, during broken home, and post-broken home. Meanwhile, the guidance obtained by the subject comes from his grandfather and lover. The implication of the results of this study is to analyze need assessment of the guidance and counseling program for the implementation of family counseling in families experiencing broken homes.